India-Japan Investment Relations: Trends & Prospectus - Geethanjali Nataraj (Indian Council for Research on International Economic Relations (ICRIER), 2010)
Though Japan had been one of the top five investors in India for long, its share in India's total FDI inflows has been dwindling since 2000. Other countries have surpassed Japan in terms of their investment and market share in the Indian economy. In this context, this study attempts to analyse the constraints on Japanese investment in India. The study finds that poor infrastructure, taxation system, procedural hassles in customs clearance, and red tapism are important factors deterring Japanese investment in India. Further, many Japanese companies have lost out to stiff competition from South Korean companies, which have been able to understand the price-sensitive nature of the Indian consumer better. It is expected that the completion of the on-going negotiations on the Comprehensive Economic Partnership Agreement (CEPA) will boost Indo-Japanese investment relations. There exist huge opportunities for Japanese investors in sectors such as biotechnology, agriculture, hydrocarbon fuels and information and communication technology.
Keywords: F1; F21; 330; Foreign direct investment; bilateral trade; Asia; Auslandsinvestition; Internationale Wirtschaftsbeziehungen; Indien; Japan